The Effect of Magneto Dielectric Material to the Performance of Rectangular Microstrip Patch Antenna - Ramek, Jude Blaise; Yee See Khee, (Evolution in Electrical and Electronic Engineering, 2021)
In moving toward to fifth generation (5G) network, many antennas are using magneto dielectric material as their substrate to fulfilled a demand of small, high performance and wideband antennas. However, the effect of the magneto dielectric material properties to the performance of the antenna are unknown. Therefore, in this research intends to investigate the effect of dielectric constant, electric loss tangent, relative permeability and magnetic loss tangent to the performance of rectangular microstrip patch antenna. The value of each property is varied so that the performance of the antenna such as return loss, gain, directivity, radiation pattern and bandwidth at 3.5 GHz can be analyzed. The simulated result is analyzed by using CST Microwave Studio software. Based on the simulation results, it is found that the antenna with higher dielectric constant value substrate is good for antenna miniaturization but it lowers down the gain, bandwidth and directivity of the antenna. While, as the relative permeability of the substrate is getting higher, it is difficult to optimize the dimension of the antenna in order to achieve resonance at 3.5 GHz. The size of the antenna also getting bigger. Besides that, it is also observed that electric and magnetic loss tangent of the substrate is proportional to the directivity of the antenna, however, it narrows the bandwidth and gain of the antenna. The outcome from the analysis has provided a guideline for antenna design using magneto dielectric material. The desired performance can be achieved by choosing suitable substrate material. For future work, the simulations should be carried out at smaller step size and wider range. Besides that, the thickness of the substrate can be varied and the performance can be analyzed.